LGBTQ parents' experiences of community youth sport: Change your forms, change your (hetero) norms. Issue 1 (February 2018) - Trussell, Dawn E.; Kovac, Laura; Apgar, Jen
Highlights: LGBTQ parents anticipated homophobia, yet found accepting youth sport communities. LGBTQ parents' faced heteronormative assumptions within community youth sport. LGBTQ parents advocated for inclusive language and program design in community youth sport. LGBTQ parents found youth sport organisations were receptive to calls for inclusion. Abstract: This interpretive study sought to critically examine lesbian, gay, bisexual, transgender, or queer (LGBTQ) parents' experiences of community organized youth sport. Using a constant comparative method of data analysis, the authors examined perspectives of participants from Australia, Canada, and the United States. Three emergent themes best reflected the parents' experiences: (a) anticipating sexual stigma and finding accepting communities; (b) confronting assumptions of heterosexuality; and (c) educating but not flag waving. Emphasis is placed on the parents intersecting social identities and notions of privilege (e.g., socio-economic resources and the ability to live in socially progressive areas), and how it altered their experiences within the community youth sport context. The findings call attention to the responsibility of youth sport organisations to create a climate of social change through inclusive language, behaviours, and program design.